2020
DOI: 10.3390/md18090482
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Print Autophagy in 2020: A Critical Review

Abstract: Autophagy is an elegant and complex biological process that has recently attracted much attention from the scientific community. The compounds which are capable of control and modulation of this process have a promising potential as therapeutics for a number of pathological conditions, including cancer and neurodegenerative disorders. At the same time, due to the relatively young age of the field, there are still some pitfalls in the autophagy monitoring assays and interpretation of the experimental data. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 156 publications
(322 reference statements)
0
6
0
Order By: Relevance
“…Overall, this study provides evidence of the potential of POE to alleviate intracellular lipid accumulation through activation of autophagy. Thus, POE, which can control this process in liver cells, could have promising potential as an alternative medical strategy for a variety of disease conditions, including NAFLD [22,40].…”
Section: Poe Alleviates Lipid Accumulation In Hepg2 Cells By Inducing Autophagymentioning
confidence: 99%
“…Overall, this study provides evidence of the potential of POE to alleviate intracellular lipid accumulation through activation of autophagy. Thus, POE, which can control this process in liver cells, could have promising potential as an alternative medical strategy for a variety of disease conditions, including NAFLD [22,40].…”
Section: Poe Alleviates Lipid Accumulation In Hepg2 Cells By Inducing Autophagymentioning
confidence: 99%
“…4C ). Since simultaneously increased protein levels of p62/SQSTM1 and LC3-II indicated dysfunction of autophagy degradation ( 44 ), these findings suggested that PPM may have exerted differential effects at different stages of autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the molecules we covered in this review eventually induce apoptosis. Certain molecules such as micropeptins and the tutuilamides A–C have demonstrated elastase inhibition properties [ 103 , 245 ], making them suitable anticancer agents because the levels of this protease are significantly elevated in various cancers [ 246 ]. Likewise, some specific depsipeptides that induce autophagy include apratoxin A, coibamide A, and plitidepsin, which induces macroautophagy via the autophagy-related protein 5–ubiquitin system [ 29 , 247 ].…”
Section: Discussionmentioning
confidence: 99%